May-Thurner Syndrome as a Rare Cause of Paradoxical Embolism in a Patient with Patent Foramen Ovale - Dominika M. Zoltowska; Guramrinder Thind; Yashwant Agrawal; Vishal Gupta; Jagadeesh Kumar Kalavakunta (Case Reports in Cardiology)
May-Thurner syndrome is an underrecognized anatomical variant that can lead to increased propensity for venous thrombosis in the lower extremities. We present a case of a 67-year-old female who presented with transient ischemic attack. Initial workup including CT scan of the head, MRI scan of the head, and magnetic resonance angiogram of the head and neck was unremarkable. A transthoracic echocardiogram with bubble study was also normal. Subsequently, a transesophageal echocardiogram was performed that revealed a patent foramen ovale with right-to-left shunt. Lower extremity duplex venous ultrasound showed no evidence of deep vein thrombosis. However, magnetic resonance venogram of the pelvis showed compression of the left common iliac vein just after its origin suggestive of May-Thurner syndrome. Hence, May-Thurner syndrome was recognized as the probable source of paradoxical embolism causing transient ischemic attack in this patient.